Repurposing drugs to fight aging: The difficult path from bench to bedside. Issue 3 (13th December 2020) - Vaiserman, Alexander; Koliada, Alexander; Lushchak, Oleh; Castillo, Manuel J.
Abstract: The steady rise in life expectancy occurred across all developed countries during the last century. This demographic trend is, however, not accompanied by the same healthspan extension. This is since aging is the main risk factor for all age‐associated pathological conditions. Therefore, slowing the rate of aging is suggested to be more efficient in preventing or delaying age‐related diseases than treat them one by one, which is the common approach in a current pharmacological disease‐oriented paradigm. To date, a variety of medications designed to treat particular pathological conditions have been shown to exhibit pro‐longevity effects in different experimental models. Among them, there are many commonly used prescription and over‐the‐counter pharmaceuticals such as metformin, rapamycin, aspirin, statins, melatonin, vitamin antioxidants, etc. All of them are being increasingly investigated in preclinical and clinical trials with the aim of determine whether they have potential for extension of human healthspan. The results from these trials are frequently inconclusive and fall short of initial expectations, suggesting that innovative research ideas and additional translational steps are required to overcome obstacles for implementation of such approaches in clinical practice. In this review, recent advances and challenges in the field of repurposing widely used conventional pharmaceuticals to target the aging process are summarized and discussed.